A Survey on Factors Affecting Knowledge and Satisfaction with Care Among Persons with Diabetes Mellitus in an Urban Health Centre and its Outreach Clinics in South India - Lovelina, Lerisha; Mukherjee, Pavan; Kumar, Vijaya; Abraham, Sunil; Rahman, Sajitha; Pricilla, Ruby Angeline (Journal of the ASEAN Federation of Endocrine Societies, 2023)
Objective. To determine the level of knowledge and factors affecting knowledge and satisfaction with diabetes care among persons with diabetes at urban health centre (UHC) and community health worker (CHW)-led outreach clinics (ORC) in South India. Methodology. A cross-sectional study was carried out using a structured questionnaire. One hundred patients at the UHC and 200 patients at the ORC were included. Results. Patients with DM of more than eight years, with co-morbidities and maintained on insulin had good knowledge at the UHC. At the ORC, participants who received education beyond the primary level and belonging to non - Hindu religion had higher knowledge. Patients at the ORC experienced better satisfaction in terms of waiting time for appointments, consultation, registration system and counselling. At the UHC, those who received primary education or those with lower educational attainment had better satisfaction. Overall, knowledge (p=0.03) and satisfaction (p=0.00001) of diabetes care was better at the ORC than at the UHC. Conclusions. Our study found better knowledge and satisfaction with diabetes care at the ORC than at the UHC. Whether or not the difference can be attributed to CHW-based clinics in the community needs to be further elucidated.